2007
DOI: 10.1038/sj.ejcn.1602633
|View full text |Cite
|
Sign up to set email alerts
|

The duration of enzyme induction in orocaecal transit time measurements

Abstract: Objective: In this study, the duration of enzyme induction provoked by unlabelled lactose ureide (LU) in orocaecal transit time (OCTT) measurements with lactose-[ 13 C]ureide ( 13 C-LU) was evaluated. Design: Experimental study. Setting: University of Rostock, Children's Hospital, Research Laboratory. Subjects: Fifteen healthy adults aged 19-54 years. Intervention: One-half gram of 13 C-LU was administered together with a continental breakfast. After 1 week, the test was repeated after pre-dosing of 5 Â 100 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
2
3
1
Order By: Relevance
“…It has been shown clinically that priming with lactose-ureide is necessary to investigate the orocecal transit time (Wutzke et al, 2007). We also confirmed that a priming dose of lactose-ureide is necessary in the breath testing of rats (Uchida et al, 2009a).…”
Section: Effects Of Primed Lactose-ureide and Lactose-ureide Containesupporting
confidence: 67%
“…It has been shown clinically that priming with lactose-ureide is necessary to investigate the orocecal transit time (Wutzke et al, 2007). We also confirmed that a priming dose of lactose-ureide is necessary in the breath testing of rats (Uchida et al, 2009a).…”
Section: Effects Of Primed Lactose-ureide and Lactose-ureide Containesupporting
confidence: 67%
“…The increase of the 13 CO 2 -enrichment in the expired air reflected the microbial degradation of DLLU. These observations of an apparently shorter OCTT after pre-dosing with chemically different sugar ureides strongly suggest a preceding induction of the enzyme activity as already claimed earlier when pre-dosing with the same ureide in its unlabelled form (Wutzke et al, 1997;Wutzke and Glasenapp, 2004;Wutzke and Schütt, 2007). Furthermore, it could be demonstrated that pre-dosing with merely 3 Â 120 mg GU as well as the equimolar dosage of 3 Â 200 mg CU is high enough to induce the enzyme activity and to give reliable results.…”
Section: Discussionsupporting
confidence: 52%
“…The observed CPDR and CPE data were also in the same order of magnitude with the values published earlier (Wutzke and Glasenapp, 2004;Wutzke and Schütt, 2007). In contrast to the measurement of the OCTT along with the mandatory pre-treatment procedure, our findings demonstrate that (except for the GU pre-dosing with a high s.d., presumably caused by an incomplete homogenization of the faeces) neither the urinary nor the faecal total CPE are affected by pre-dosing with both unlabelled ureides ( Table 2).…”
Section: Discussioncontrasting
confidence: 33%
See 2 more Smart Citations